Financial Management Research Trends in Global Perspective: A Scopus-Based Bibliometric Analysis Using VOSviewer (2020–2025) - Asriani Asriani; Yulinda L. Ismail; Abdul Rahman Mus; Masdar Masud (SEAN Institute, 2026)
This study aims to analyze global research trends in financial management during the period 2020–2025 using a bibliometric approach based on the Scopus database. The research employs quantitative bibliometric methods combined with network visualization analysis using VOSviewer to identify patterns of publication growth, leading authors, influential journals, countries' contributions, and emerging research themes. A total of selected documents were extracted using relevant keywords related to financial management and screened based on inclusion criteria such as document type, language, and publication year. The findings reveal a significant increase in financial management research, particularly after 2020, driven by global economic uncertainty, digital transformation, and financial technology innovation. The most dominant research themes include financial performance, corporate governance, sustainability, fintech, and risk management. Network visualization indicates strong collaboration among developed countries, while emerging economies show increasing contributions. Furthermore, keyword co-occurrence analysis highlights a shift toward digital finance, ESG (Environmental, Social, and Governance), and financial resilience. This study contributes to the literature by providing a comprehensive overview of the intellectual structure and development of financial management research, offering valuable insights for researchers, academics, and policymakers in identifying future research directions and strategic priorities.